Effect of rabbit gastrointestinal stasis (RGIS) on the fecal microbiota of pet rabbits (Oryctolagus cuniculus) - Faith M. Rahic-Seggerman; Cayla Iske; Jennifer Graham; Nicole Furst; Stephan Schmitz-Esser; Micah R. Kohles (PLoS ONE, 2025)
Rabbit (Oryctolagus cuniculus) gastrointestinal stasis syndrome (RGIS) is defined as reduced motility of any part of the digestive tract that can lead to impaction and death if left untreated. This study aimed to describe the effect of RGIS on the fecal microbiota of client-owned pet rabbits. Fecal samples from healthy rabbits and rabbits displaying RGIS were obtained and the symptomology of the rabbits was recorded along with any medical intervention. The health outcomes were as follows: 1) Healthy rabbits (Healthy, n = 21), and 2) Rabbits that displayed symptoms of RGIS, were treated, and recovered (RGIS, n = 22). The fecal samples were analyzed using 16S rRNA and 18S rRNA gene amplicon sequencing to characterize the bacterial and eukaryotic microbial communities, respectively. In the 16S rRNA amplicon dataset, two bacterial genera were found in higher abundance in rabbits with RGIS: Clostridium sensu stricto 1 and an unclassified genus in the Enterobacteriaceae family. Likewise, five genera were found in higher abundance in healthy rabbits. The yeast Cyniclomyces guttulatus dominated the eukaryotic microbiota in all rabbits. RGIS is one of the most common issues in clinical practice. This study is the first to perform detailed characterization of the effects of RGIS on the domestic rabbit’s bacterial and eukaryotic fecal microbiota. The results demonstrate a significant change in the relative abundance of seven bacterial genera associated with RGIS. Future research is necessary to elucidate the potential role of these microorganisms in RGIS. In the long-term, treatments targeting the restoration of the physiological gastrointestinal microbiota should be developed.